Robert's Uterus versus juvenile cystic adenomyoma - Diagnostic and therapeutic challenges - Case report and review of literature - Reeta Mahey; Rohitha Cheluvaraju; Supriya Kumari; Garima Kachhawa; Archana Kumari; Monika Rajput; Neerja Bhatla (Wolters Kluwer Medknow Publications, 2023)
This case report highlights the diagnostic dilemma and therapeutic challenges encountered while managing adolescent girls with progressive dysmenorrhoea and management of Robert's uterus. Two girls aged 20 years and 13 years presented with severe progressive dysmenorrhoea. In the first case, laparoscopy revealed juvenile cystic adenomyoma (JCA) of 3 cm × 3 cm on the left side anteroinferior to the round ligament. Laparoscopic resection of the lesion was done, and histopathology revealed features of adenomyosis. In the second case, there was a globular enlargement of the right half of the uterine body with round ligament and adnexa attached to the lesion (Robert's uterus). In view of severe symptoms, complete resection of the lesion and partial resection of hemi-uterus was done, followed by myometrial defect closure. Both cases were initially diagnosed as JCA, and the final diagnosis was made on laparoscopy. Both girls had complete symptomatic relief from the next menstrual cycle and have been under follow-up for 24 months and 18 months, respectively. Due to the rarity of conditions, Robert's uterus and JCA are usually misdiagnosed with each other or with other Mullerian anomalies such as a non-communicating unicornuate uterus. Radiologists and clinicians should be aware of these different pathologies causing similar symptoms. Understanding the pathology, early diagnosis, timely referral and correct surgical procedure are emphasised to improve reproductive outcomes.